PENGEMBANGAN INSTRUMEN ASESMEN KOGNITIF BERBASIS KETERAMPILAN BERPIKIR KRITIS PADA MATERI ASAM BASA DI SMA NEGERI 3 BENGKULU TENGAH - Rovi Atahilah; Rina Elvia; Febrian Solikhin (ALOTROP, 2022)
This study aims to develop a cognitive instrument based on critical thinking skills on acid-base material based on needs analysis in schools. This type of research is research and development with the ADDIE model, where researchers only carry out until the implementation stage. The sample of this research is class XI IPA 1 opening 29 people. The sampling technique used was purposive sampling. Data analysis using item validation test and reliability test using Lawshe theory and Rasch model as well as testing students' critical thinking skills. The results of developing the Critical Thinking instrument show that it is valid and has a very high reliable value. Valid questions from validation are 18 questions from 24 questions developed, valid questions from empirical validation 8 questions from the expert validation stage. The results of the trial for critical thinking obtained 3.4% very critical, namely 1 critical person, 51.7% critical, namely 15 students, 37.9% critical, namely 11 students and 7% less critical, namely 2. Average value of thinking skills The overall critical score of students is 62.2% which is in the critical category. For results based on Ennis' critical thinking indicators, 76.6% of questions focus indicators are included in the critical category, 59.3% of indicators determine a source including the critical enough category, critical indicators analyze arguments 66.2% are included in the critical category, indicators define terms and considering a definition 52.4% is included in the quite critical category, the ID indicator assumptions 69.7% is included in the critical category, the indicator observes and considers the observation results 52.4% is included in the quite critical category, the indicator answers challenges 61.4% includes critical category, and indicators make and determine the results of the consideration 59.3% including quite critical category.